Analysis of energy efficiency of the intrafarm biofuel workshop (the case of production of motor fuel from colza oilseeds) - V. A. Kolos; Yu. N. Sap’Yan; P. M. Pugachev (Сельскохозяйственные машины и технологии, 2015)
When studying problems of production of biofuels (BF) from various raw materials the great value is attached to power criteria: particular - to resource intensity, power consumption, energy content and generalized - to energy consumption, power potential of products, coefficients of full and direct energy efficiency (CEE and CDEE) of BF-technology. In many European countries the natural rape oil (RO), and also the mixed fuels (MF) with addition of oil diesel (DF) are widely applied as motor BF. Calculation and the analysis of criteria of energy efficiency of production of RO and MF (60 percent of DF) taking into account the full life cycle of resources were carried out. Due to technical and economic data of the project of the BF-shop created by All-Russian Research Institute of Mechanization for Agriculturefor JSC breeding enterprise Lazarevskoye in Tula region there were received rather high values of CEE of stages of direct oilseeds processing into RO and preparations of MF - respectively 7.13 and 4.98 by CDEE 24.2 and 61.8, and also CDEE of all BF-technology - 8.4 and 22.3. The option with use of a by-product (oil seeds cake) for the thermal purposes of economy or by fuel pellets production at an additional stage will allow increase CEE of RO to 2.82, and MF to 3.58 at CDEE respectively 15.6 and 40.9 percent. These data testify to high power profitability of production of RO and MF, however on CEE they are inferior to oil DF (1.57 and 2.61 again 4.2). Further increase of energy efficiency of BF-shop will be provided by realization of power potential of the second by-product of BF-technology (rape straw) in the form of separate energy resource or in common with cake. The last option surpasses option of production of RO and MF without power application of by-products in energy efficiency, respectively, by 246 and 78 percent. For information support of a power assessment of processes and technologies with use of products of this BF-shop values of their power equivalents are presented.